2017
DOI: 10.1038/ncomms14654
|View full text |Cite
|
Sign up to set email alerts
|

E3 ligase FBXW7 is critical for RIG-I stabilization during antiviral responses

Abstract: Viruses can escape from host recognition by degradation of RIG-I or interference with the RIG-I signalling to establish persistent infections. However, the mechanisms by which host cells stabilize RIG-I protein for avoiding its degradation are largely unknown. We report here that, upon virus infection, the E3 ubiquitin ligase FBXW7 translocates from the nucleus into the cytoplasm and stabilizes RIG-I. FBXW7 interacts with SHP2 and mediates the degradation and ubiquitination of SHP2, thus disrupting the SHP2/c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 50 publications
3
53
0
Order By: Relevance
“…RIG-I activity is significantly modulated through ubiquitylation processes mediated by several E3 ligases [34,[44][45][46][47], differentially expressed depending on the tumor context [48,49]. MEX3C, TRIM4 and TRIM25 are the most important E3 ligases for positive regulation of RIG-I activity in response to viral infection, whereas RNF122 and RNF125 have been described to mediate the ubiquitin-dependent degradation of this cytosolic innate immune receptor.…”
Section: Discussionmentioning
confidence: 99%
“…RIG-I activity is significantly modulated through ubiquitylation processes mediated by several E3 ligases [34,[44][45][46][47], differentially expressed depending on the tumor context [48,49]. MEX3C, TRIM4 and TRIM25 are the most important E3 ligases for positive regulation of RIG-I activity in response to viral infection, whereas RNF122 and RNF125 have been described to mediate the ubiquitin-dependent degradation of this cytosolic innate immune receptor.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293T cells (American Type Culture Collection [ATCC], CRL-11268) were maintained in DMEM medium, and thioglycolate-elicited mouse peritoneal macrophages (BD, 3190383; Merck, 1.08191.0500) were cultured in RPMI 1640 medium with 10% (vol/vol) FCS. BMDMs were generated using BM from femurs and tibiae of 6-to 8-week-old mice (25).…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 is also reported to regulate lipid metabolism (22), target osteogenic and chondrogenic transcriptional factors (23), interact with parkin, and play important roles in Parkinson's disease (24). Our previous study showed that FBXW7 is critical for promoting innate antiviral immunity by mediating the ubiquitination of SHP2 (25). However, the function and mechanisms of FBXW7 in inflammation responses have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…For immunoblot analysis, cells were lysed with cell lysis buffer (Cell Signaling Technology; 9803) supplemented with a protease inhibitor "cocktail" (Sigma; P8340). The antibodies for immunoblot analysis were used as we previously described (17).…”
Section: Immunoblot and Immunoprecipitation Analysismentioning
confidence: 99%